Memorandum of the Government of the Democratic Federative Yugoslavia concerning the question of the Julian March and other Yugoslav territories under Italy. (1946)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: territoriale kwesties; Trieste; Venezia Giulia; Istrië; Slovenië